2019
DOI: 10.1002/app.47522
|View full text |Cite
|
Sign up to set email alerts
|

Sponge‐like chitosan‐based nanostructured antibacterial material as a topical hemostat

Abstract: In this study, chitosan/alginic acid/zinc oxide (CHI/AA/ZnO) nanostructured hydrogel sponges were fabricated by incorporating ZnO nanoparticles (<100 nm) into polymer matrix to develop a new potential biomaterial for hemorrhage control. For this purpose, the crosslinked CHI/AA/ZnO nanostructured sponges were synthesized by freeze‐drying technique. Genipin was used as a crosslinker. The prepared chitosan‐based sponges were characterized by Fourier transform infrared spectroscopy, X‐ray diffraction, and scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…Bal‐Ozturk et al reported chitosan/alginic acid/zinc oxide (CHI/AA/ZnO) nanostructured hydrogel sponges that could be used as an antibacterial hemostat. ZnO in the sponges increased antibacterial properties, and the hydrogel sponge was biocompatible in vitro and in vivo (Bal‐Ozturk et al, ). Fathi et al () synthesized zeolite‐loaded alginate–chitosan hydrogel beads where zeolite served as blood absorbent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bal‐Ozturk et al reported chitosan/alginic acid/zinc oxide (CHI/AA/ZnO) nanostructured hydrogel sponges that could be used as an antibacterial hemostat. ZnO in the sponges increased antibacterial properties, and the hydrogel sponge was biocompatible in vitro and in vivo (Bal‐Ozturk et al, ). Fathi et al () synthesized zeolite‐loaded alginate–chitosan hydrogel beads where zeolite served as blood absorbent.…”
Section: Introductionmentioning
confidence: 99%
“…Various forms (e.g., solid sheets, sponges, particles/fibers) of biomaterials (e.g., collagen, keratin, chitosan, polyurethane) have been investigated for use as an effective hemostat (Peng, 2010;Tomizawa, (CHI/AA/ZnO) nanostructured hydrogel sponges that could be used as an antibacterial hemostat. ZnO in the sponges increased antibacterial properties, and the hydrogel sponge was biocompatible in vitro and in vivo (Bal-Ozturk et al, 2019). Fathi et al (2018) synthesized zeolite-loaded alginate-chitosan hydrogel beads where zeolite served as blood absorbent.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, the number of studies with metallic nanostructures increases due to concerns on antibiotic resistance. It is known that a variety of metals including silver, gold, copper, titanium, zinc oxide, iron oxide, and magnesium oxide have antibacterial activities, 31,32,84,85 and are widely used in design of novel wound dressing materials.…”
Section: Inorganic Nanostructuresmentioning
confidence: 99%
“…It is known that a variety of metals including silver, gold, copper, titanium, zinc oxide, iron oxide, and magnesium oxide have antibacterial activities, 31,32,84,85 and are widely used in design of novel wound dressing materials.…”
Section: Inorganic Nanostructuresmentioning
confidence: 99%
“…[200,201] SiO 2 ,ZrO 2 und TiO 2 werden ebenfalls zu diesem Zweck in Gerüstverbindungen und Perlkatalysatoren eingesetzt. [202,203] Anorganische Oxide dienen zur Funktionalisierung dieser Gerüste und Perlen, zum Beispiel ZnO füre ine antibakterielle und photokatalytische Aktivität, [204] TiO 2 fürp hotokatalytische und katalytische Aktivitäten, [205] Fe 3 O 4 ,u me ine Sammlung durch Magnetkräfte zu ermçglichen, [206] und Zeolithe zur Adsorption und als Strukturgerüste fürd ie Tr ocknung bei Umgebungsdruck. [180] Komposite mit lumineszierenden Materialien haben ein großes Potenzial fürs ensorische/bildgebende Anwendungen wie das Gas-responsive rotemittierende YVO 4 :Eu 3+ , [199] das IR-zu-vis-aufkonvertierende NaY-F 4 :Yb 3+ ,Er 3+ [207] sowie Eu 3+ -und Tb 3+ -Komplexe mit SiO 2 .…”
Section: Kompositeunclassified